DESAIN PERANGKAT MONITORING JUMLAH PENGUNJUNG PADA RUANG PUBLIK BERBASIS CITRA MENGGUNAKAN METODE BINARY IMAGE COMPARISON - A. Edeth Fuari Anatasya; Pujianti Wahyuningsih; Abdul Jalil (Electro Luceat, 2022)
The purpose of this study is to build a software and hardware design that will be used to calculate and monitor the number of visitors in public space based on the image processing technique using the Binary Image Comparison (BIC) method. In the BIC method, there is a master binary image value that will be compared with the color binary image value which is used as a determinant in calculating the number of people entering and leaving a public space. The camera as an input device is used to capture image objects, then it will be processed using a Raspberry Pi, then the output from this device is an LCD to display the number of visitors, a buzzer to give a warning when the number of visitors has met the maximum limit, and a led indicator. The software used to process image data is using the Python programming language and the OpenCV library. The result of this research is the design of software and hardware that will be used to monitor the number of visitors in public space based on image processing technique using the BIC method